Stochastic simulation of ship airwake in helicopter shipboard operation - Taymourtash, N.; Zanotti, A.; Gibertini, G.; Quaranta, G. (My University, 2022)
For the development of a high-fidelity simulation environment for shipboard operations, modelling the unsteady aerodynamic loads caused by mutual interaction of the rotor wake and ship airwake is of great importance. In this paper, a stochastic modelling approach is proposed which can significantly reduce the computational cost required for real-time implementation of turbulent airwake obtained by standard approaches based on time-accurate Computational Fluid Dynamics. Starting from the availability of measured data collected in a scaled wind tunnel experiment with a rigid rotor, it has been possible to identify a model for the airspeed disturbance generated by the mutual interaction between the rotor and the ship airflow that results in the same load spectrum measured in the experiment. First Frequency Response Functions are estimated to represent the aerodynamic loads of the rotor. Then, these functions are used to identify the frequency response of an external disturbance vector, composed of vertical, lateral and longitudinal velocity components, able to return the same load components on a model of the rotor. The identified disturbance speed components that represent the effect of the unsteady interaction can then be incorporated into the model of a full-scale flight simulator through a set of Auto-Regressive filters designed for each particular wind condition and rotor position over the deck. Exciting the AR filters by white noise results in the same frequency content as the identified gust. Validation is performed for two hovering positions over the deck of SFS1 in three different wind conditions. Comparing the unsteady loads with the experimental results demonstrates that this stochastic modelling approach is able to predict the unsteadiness across the frequency bandwidth which affects the pilot activities